Connection between personal perfectionism and efficiency of students’ learning activities - Romanovskyi, O. G.; Pidbutska, N. V.; Shtuchenko, I. Ye.; Knysh, A. Ye. (Foundation Pro Scientia Publica, Poland, 2020)
The level of learning efficiency of students depends on the pace of learning, the quality of learning, the ability to generalize and synthesize new information. Positive statistically significant correlations were found between perfectionism and student learning efficiency.
Keywords: perfectionism; learning efficiency; learning activities; students; professional development; adequate goal setting